La ayuda médica a morir como derecho fundamental. Comentario crítico de la sentencia de la Corte Suprema de Canadá de 6 de Febrero de 2015, asunto Carter v. Canadá (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
In its judgment in Carter v. Canada, on February 6, 2015, the Supreme Court of Canada has come to recognize that medical help to die (physician-assisted suicide and active euthanasia direct) is a fundamental right. Examining the validity of the criminal law prohibiting assisted suicide (including hospice), has concluded that it is unconstitutional to deny medical help to die adult patients relevant to the request as a result of an illness or disability that causes them permanent and irreversible intolerable suffering. This paper analyzes and critically evaluates this relevant decision.
Keywords: physician-assisted suicide; physician-assisted suicide; Euthanasia; Euthanasia; Informed consent; Informed consent; Patient's right to make decisions at the end of his life; Patient's right to make decisions at the end of his life; Legal problems of euthanasia in Canada; Legal problems of euthanasia in Canada